A transição de adolescentes com HIV/AIDS para a clínica de adultos: um novo desafio - Machado, Daisy Maria [UNIFESP] (2010)
OBJECTIVE: To review the literature on transition from pediatric to adult-oriented health care and discuss this issue in the specific context of chronic conditions. SOURCES: MEDLINE and LILACS were searched for relevant English and French-language articles published between 1990 and 2010. SUMMARY OF THE FINDINGS: The transition of adolescents with chronic diseases from pediatric care to adult-oriented services has been a growing concern among pediatric specialties. In recent years, young people living with HIV/AIDS have begun to reach adulthood, giving rise to several challenges. The studies reviewed herein discuss such relevant topics as: the difference between transfer, an isolated event, and transition, a gradual process; the transition models used in different services; the importance of transitioning in a planned and individualized manner; the need for comprehensive interaction between pediatric and adult-oriented care teams; the importance of joint participation of adolescents, their families, and health professionals in the process; barriers to and factors that promote successful transitions; and the special needs of adolescents with HIV/AIDS in this important period of life. CONCLUSIONS: Several authors agree that transitioning adolescents to adult-oriented health care should be a gradual process not determined by age alone. It requires a plan established with ample dialogue among adolescents, their families, and pediatric and adult care teams. However, there is little evidence to support any specific model of health care transition. This should prompt researchers to conduct more prospective studies on the theme, especially in more vulnerable groups such as adolescents living with HIV/AIDS.